Le voyage d’Europe au fil des siècles / Europa’s Journey through the Ages - Alvino, Maria Consiglia; Di Franco, Matteo; Rossetti, Federica; Rubulotta, Gabriella (Brepols, 2021)
The myth of Europa, first attested in the eighth century <span class=